Yankee doodle dixie [large type] - Patton, Lisa (Thorndike Press large print core series., 2012)
Having watched her life turn into a nor'easter, 34-year-old LeeLee Satterfield is back home in the South, ready to pick back up where she left off. But that's a task easier said than done. LeeLee's a single mom, still dreaming of the Vermonter who stole her heart. Accompanied by her three best friends who pepper her with advice and peach daiquiris, LeeLee opens another restaurant and learns she has to prove herself yet again.